Corporate identity as one of the important management activity - Strišš, Jozef; Vodák, Jozef (Univerzita Pardubice, 2006)
Paper is dealing with Corporate identity (CI) as one of the important management processes in marketing. We try to show CI history, principles, possibilities and experiences of using it in the context and conditions of Slovak republic. This article offers a set of useful rules for successful implementation CI in the organisation. This paper characterises individual parts of Corporate identity as the part of managerial process known as effective marketing communication of those organizations that want to increase their competitiveness.
Corporate identity jako jedna z dôležitých činností manažmentu
Keywords: corporate identity (CI); podniková identita; Marketing; Slovenská republika